Class Differences in Cohabitation Processes - Sassler, Sharon (2011)
Despite the burgeoning cohabitation literature, research has failed to examine social class variation in processes of forming and advancing such unions. Drawing upon in-depth interviews with 122 working- and middle-class cohabitors, we examine the duration between dating and moving in together, reasons for cohabiting, and subsequent plans. Transitions to cohabitation are more rapid among the working class. Respondents often cohabited for practical reasons—out of financial necessity, because it was convenient, or to meet a housing need. Regardless of social class status, few couples move in together as a “trial marriage.” Nonetheless, middle-class cohabitors were more likely to have become engaged than their working-class counterparts. Our findings indicate the need to reassess common beliefs regarding the role served by cohabitation and suggest that cohabitation has become another location where family outcomes are diverging by social class.